Suppressor of cytokine signaling 3 inhibits head kidney macrophage activation and cytokine expression in Scophthalmus maximus - Zhang, Min; Xiao, Zhi-zhong; Sun, Li (Developmental & Comparative Immunology, 2011)
Proteins of the suppressor of cytokine signaling (SOCS) family function as inducible feedback inhibitors of cytokine signaling via the JAK/STAT pathway. Although several SOCS isoforms have been identified in teleosts, their immunological functions remain largely unknown. In this study, we identified in turbot Scophthalmus maximus a SOCS homologue (named SmSOCS3) of the mammalian SOCS3 type. The deduced amino acid sequence of SmSOCS3 contains 205 residues and shares extensive overall identities (60-82%) with those of known fish SOCS3. In silica analyses revealed that, like typical SOCS3. SmSOCS3 possesses a kinase inhibitor region (KIR). a Src homology 2 (SH2) domain, and a SOCS box domain. Under physiological conditions SmSOCS3 expression was detected, in increasing order, in blood, brain, heart, kidney, liver, spleen, muscle, and gill. Experimental infection of turbot with a bacterial pathogen induced significant SmSOCS3 expression in kidney, spleen, liver, and gill in time-dependent manners. Examination of SmSOCS3 expression in head kidney (HK) macrophages showed that SmSOCS3 transcription was significantly upregulated in the presence of purified recombinant TNF-alpha. On the other hand, SmSOCS3 overexpression in HK macrophages inhibited the transcription of TNF-alpha as well as IL-1 beta and CC-chemokine. In addition, SmSOCS3 overexpression significantly reduced macrophage respiratory burst activity, nitric oxide production, and bactericidal activity. Taken together, these results suggest that SmSOCS3 is a cytokine-inducible suppressor of pro-inflammatory cytokine signaling in HK macrophages and that regulated expression of SmSOCS3 is required for optimal innate immune response against bacterial infection. (C) 2010 Elsevier Ltd. All rights reserved. Proteins of the suppressor of cytokine signaling (SOCS) family function as inducible feedback inhibitors of cytokine signaling via the JAK/STAT pathway. Although several SOCS isoforms have been identified in teleosts, their immunological functions remain largely ...